Combined pulsed dye and CO2 lasers in the treatment of angiolymphoid hyperplasia with eosinophilia. Issue 6 (August 2016) - Sagi, Lior; Halachmi, Shlomit; Levi, Assi; Amitai, Dan; Enk, Claes; Lapidoth, Moshe
Abstract Angiolymphoid hyperplasia with eosinophilia (ALHE) is an uncommon dermatosis of unknown etiology that manifests as characteristic red nodules and papules with a predilection for the scalp and periauricular region. Treatment is required for both esthetic and functional reasons, as lesions may ulcerate and bleed. Many treatment approaches have been reported, including excision, systemic medical approaches, topical or intralesional therapies, and non-invasive modalities including cryotherapy, electrosurgery, and laser. Treatments have exhibited variable efficacy, and the recurrence rate is 100 %. We report the combination of pulsed dye laser and CO2 laser in the treatment of ALHE in 14 patients. All patients exhibited clinical response after a mean of 2.4 ± 0.4 treatment sessions. The clinical efficacy of the combined treatment, together with its well-tolerated nature, render the use of pulsed dye laser in combination with CO2 laser, a viable treatment for debulking ALHE lesions. Ongoing maintenance treatments are needed to due to the high degree of relapse.